2008
DOI: 10.3174/ajnr.a1262
|View full text |Cite
|
Sign up to set email alerts
|

Intradural Hemangiopericytoma of the Lumbar Spine: A Rare Entity

Abstract: SUMMARY:We report a case of a patient with an intradural hemangiopericytoma of the lumbar spine and the unusual MR angiography (MRA) and spinal angiography findings of arteriovenous shunting with spinal venous congestion. We highlight the concordance of the unusual MRA and angiographic findings and their relationship to combined endovascular and surgical therapy. H emangiopericytomas, initially described by Stout and Murray, 1 are vascular tumors derived from pericytes, the smooth muscle cells that control the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…The first intradural case was reported in 1961 by Kruse [11]. Since then, 23 cases have been reported, including our four present cases [4][5][6][7][8][9][10][11][12][13][14]. The occurrence of HPCs has been reported throughout the cervical, thoracic and lumbar spine, but the cervicothoracic region appears to have the greatest prevalence ( Table 2).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…The first intradural case was reported in 1961 by Kruse [11]. Since then, 23 cases have been reported, including our four present cases [4][5][6][7][8][9][10][11][12][13][14]. The occurrence of HPCs has been reported throughout the cervical, thoracic and lumbar spine, but the cervicothoracic region appears to have the greatest prevalence ( Table 2).…”
Section: Discussionmentioning
confidence: 89%
“…Betchen et al [5] reported that extradural tumors are associated with more pain than intradural tumors. In a review of the literature, 5 out of the 19 patients had pain complaints involving intradural lesions [4,8,9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Histologically, hemangiopericytoma arises from pericytes of Zimmerman or pericapillary cells and can occur anywhere where capillaries are found. 2,8,9 It has been classified as a mesenchymal tumor of the meninges and further subclassified into 2 histologic types, hemangiopericytoma and anaplastic hemangiopericytoma (corresponding to WHO grades II or III) by the WHO in 2007. 10 The literature on CT and MR imaging of intracranial meningeal hemangiopericytomas is currently limited.…”
mentioning
confidence: 99%
“…HPCs in the spine may involve the structures of the vertebra and the spinal canal, including the extradural and intradural space. Our search of the literature showed that 140 cases of HPC in the spine had been reported (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(49)(50)(51)(52)(53)(54)(55)(56), and 64 cases were extradural (2, 4-6, 8-10, 15, 20-22, 24, 25, 27, 28, 31, 32, 34, 35, 37, 40-42, 44-46, 49, 51, 53-55) (Table I). Here we present a case of primary HPC invasion in the cervicothoracic spine, as well as presenting a review of the literature.…”
Section: Introductionmentioning
confidence: 99%